2016
DOI: 10.1021/acs.jpcb.6b08339
|View full text |Cite
|
Sign up to set email alerts
|

Does Proton Conduction in the Voltage-Gated H+ Channel hHv1 Involve Grotthuss-Like Hopping via Acidic Residues?

Abstract: Hv1s are ubiquitous highly selective voltage-gated proton channels involved in male fertility, immunology, and the invasiveness of certain forms of breast cancer. The mechanism of proton extrusion in Hv1 is not yet understood, while it constitutes the first step toward the design of high-affinity drugs aimed at this important pharmacological target. In this contribution, we explore the details of the mechanism via an integrative approach, using classical and QM/MM molecular dynamics simulations of a monomeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 70 publications
0
39
0
Order By: Relevance
“…In our view and experience the challenge is not as overwhelming as might be concluded from some studies. For example, Dudev et al (13) suggested that only all-electron calculations be used for studies of Hv1, while van Keulen et al (15) presumed that EVB-type models have only been used for PT between water molecules (that might be true for some studies, e.g. ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our view and experience the challenge is not as overwhelming as might be concluded from some studies. For example, Dudev et al (13) suggested that only all-electron calculations be used for studies of Hv1, while van Keulen et al (15) presumed that EVB-type models have only been used for PT between water molecules (that might be true for some studies, e.g. ref.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this study has not explored the effect of the channel opening or the effect of ionized residues beyond the limited cluster (see also discussion in ref. 15). Furthermore, the barriers for the proton movement toward the central cluster were not studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Röthlisberger and coworkers studied the proton permeation pathway of the human Hv1 (hHv1) proton channel embedded in a palmitoyl‐oleoyl‐phosphatidyl choline membrane using an integrated approach, combining QM/MM and classical MD simulations. The most crucial mechanism steps (the sequential proton jumps) have been studied using QM/MM/MD.…”
Section: Models and Methodologiesmentioning
confidence: 99%
“…In a homology model of H V 1 proposing a PT chain including six carboxylates, spontaneous PT occurred whenever H 3 O + approached Asp or Glu (van Keulen et al . ).…”
mentioning
confidence: 97%